Preventing Advanced Stages of Disease in Samoa: A Literature Review - Annette Kaspar; Aleki Fuimaono; Shaun Mauiliu; Sione Pifeleti; Junior Posini (Disease Prevention and Public Health Journal, 2021)
Background: Surgeons are scarce in the Pacific Islands, and improvements to public and primary health care services should reduce the burden of avoidable surgical interventions. Three communicable and non-communicable diseases of public health concern in Samoa are filariasis, childhood overweight/obesity, and Helicobacter pylori (H. pylori)-induced gastric cancer. Strengthening existing public and primary health care strategies for these issues should, in turn, reduce the avoidable surgical burden of Hydrocelectomy for filarial hydrocele, in-situ pinning for Slipped Upper Femoral Epiphysis (SUFE), and endoscopic Esophago-Gastro-Duodenoscopy (EGD) for the differential diagnosis of H. pylori-induced gastric pathologies. This study aimed to perform a literature review of these conditions requiring surgical intervention in the Pacific Islands to contribute recommendations to the current public and primary health care activities in Samoa.  Method: A literature review was conducted using the PubMed and ScienceDirect databases. The primary search strategy utilized the terms and keywords “Pacific Islands”; “Filarial Hydrocele”; “SUFE”; “H. pylori-induced gastric pathology”; and their relevant synonyms. Inclusion criteria: the study population were Pacific Islanders residing in the Pacific Islands, and the study investigated presentation, etiology, epidemiology, treatment, and/or management for the three diseases of interest. Articles published before 2000 were excluded.  Results: There was only one journal article that met the inclusion criteria.  There is virtually no research literature on the current state of these preventable surgical conditions among the population residing in the Pacific Islands.  Conclusion: Data are needed to inform evidence-based policy formulation and implementation. The surgical voice should positively contribute to public health efforts.